Estado del arte de los planes de ordenamiento del recurso hídrico en Colombia con énfasis en los índices de calidad del agua (2020)
In the present research, a diagnosis is made about the Water Resource Management Plans (WRMP) with emphasis on the water quality indexes (WQI) implemented in them, through the information gathered from the websites of the Regional Autonomous Corporations (RAC), obtaining that only 30.30% of the RACs have WRMPs published on their websites. Likewise, 58 PORHs have been done in the country. From these WRMPs, information was obtained about the implemented water quality indexes, in order to recognize if the water quality index recommended by IDEAM in the Methodological Guide for the elaboration of WRMPs and used in the National Water Study (ENA) was used or if, on the contrary, a different index was implemented. The results of this review allowed to identify that only 37.50% of the RACs implement the index recommended by IDEAM. Additionally, it was obtained that for the 62.50% of the RACs that implemented a different index from the IDEAM one, 55.17% of them could implement it in case they required it from the Environmental and Sustainable Development Ministry